The Bulgarian elites after the Byzantine conquest. 1018-1041 - Dudek, Jarosław (Balcanica Posnaniensia. Acta et studia, 2020)
Emperor Basil II, conquering Bulgaria in 1018, divided it into a province managed by Byzantine governors. The Bulgarian church remained under the authority of local priests. Members of the ruling Kometopouloi family received palace titles and appanages, while the other Bulgarian nobles maintained their possessions while serving in the imperial army. After two decades by minister John of Orphanotrophos, attempt to reduce their significance in local military structures and the property tax burden led to the creation of Peter Deljan in 1040-1041. The resignation of Byzantine authorities from damaging the prestige of the Bulgarian aristocracy contributed to the relief of the uprising.